2021
DOI: 10.1016/j.crtox.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting molecular mechanisms, pathways, and health outcomes induced by Juul e-cigarette aerosol chemicals using the Comparative Toxicogenomics Database

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…To predict potential drugs that may prevent and treat CNT-induced lung cancer, the Comparative Toxicogenomics Database (CTD, ; accessed on 12 October 2021) [ 32 ] was searched to obtain the chemical interactions of hub lncRNAs and pseudogenes associated with CNT exposure. Only chemical drugs that reversed the expression levels of lncRNAs and pseudogenes and involved in cancer initiation and development were screened (that is, if the lncRNA was upregulated, we selected the drugs that decreased its expression levels).…”
Section: Methodsmentioning
confidence: 99%
“…To predict potential drugs that may prevent and treat CNT-induced lung cancer, the Comparative Toxicogenomics Database (CTD, ; accessed on 12 October 2021) [ 32 ] was searched to obtain the chemical interactions of hub lncRNAs and pseudogenes associated with CNT exposure. Only chemical drugs that reversed the expression levels of lncRNAs and pseudogenes and involved in cancer initiation and development were screened (that is, if the lncRNA was upregulated, we selected the drugs that decreased its expression levels).…”
Section: Methodsmentioning
confidence: 99%
“…SwissTargetPrediction allows us to estimate the most probable macromolecular targets of a small molecule [ 25 , 26 ]. The CTD was used to screen for genes associated with UC [ 27 ]. For further confirmation, AutoDock Vina, a widely cited open-source molecular docking software [ 28 ] was used, and the final docking results suggested that PKC-θ might be the target protein of anemonin.…”
Section: Discussionmentioning
confidence: 99%
“…The NetworkAnalyst is used to construct a protein–chemical interaction network. The protein–chemical interaction comes from the Comparative Toxicogenomics Database ( 26 ), which contains the interactions between chemical substances and genes in the literature.…”
Section: Methodsmentioning
confidence: 99%